Fortunado's, Desperado's and Clandestino's in Diaspora Labour Markets: The Circular 'Homo Mobilis' - Karima Kourtit; Peter Nijkamp; Masood Gheasi (Global Labor Organization (GLO), 2017)
Demographic patterns in our world (e.g., aging processes, birth and death rates) are increasingly influenced by migration movements. A rising number of people is `on the move', in search of a better fortune elsewhere. It is noteworthy that nowadays many migration movements do not show anymore stable patterns, but reflect a high degree of dynamics, for instance, in the form of return migration, circular and temporary migration, or chain migration. There is also a great heterogeneity in the motivations of many migrants that may have significant impacts on the migration choice, the destination place, the migrant's status, and the duration of stay. Consequently, return migration, temporary migration and circular migration have in recent years become important research and policy issues. This note offers a short review of the dilemma's and assessment issues inherent in the effects of non-structural or temporary migrants (so-called `movers') on host economies. Particular attention will be paid to circular migration policy in Europe as a vehicle to both mitigate temporary tensions on regional labor markets of host economics and to provide a solid base for sustainable growth in the sending countries. Various research and policy challenges are outlined as well.
Keywords: 330